Use of fecal microbiome to understand the impact of housing conditions on metabolic stress responses in farmed saltwater crocodiles (Crocodylus porosus) - Beale, David J.; Nguyen, Thao V.; Dyall, Tim; van de Kamp, Jodie; Bissett, Andrew; Hewitt, Leisha; Small, Alison H. (Frontiers in Veterinary Science, 2025)
IntroductionUnderstanding the impact of housing conditions on the stress responses in farmed saltwater crocodiles (Crocodylus porosus) is crucial for optimizing welfare and management practices.MethodsThis study employed a multi-omics methodology, combining targeted and untargeted LC–MS for metabolite, lipid, and hormone profiling with 16S rRNA gene sequencing for microbiome analysis, to compare stress responses and changes in fecal samples of crocodiles housed in single versus group pens. Metabolic responses to a startle test were evaluated through multivariate analysis, and changes post-stress were examined.ResultsA total of 564 metabolic features were identified. Of these, 15 metabolites were linked to the cortisol biosynthesis pathway. Metabolite origin analysis showed that 128 metabolites originated from the host, 151 from the microbiota, and 400 remained unmatched. No significant differences in fecal corticosterone levels were observed between single and group pens. However, metabolic profiling revealed distinct differences in stress responses: single pen crocodiles exhibited downregulation of certain compounds and upregulation of others, affecting pyrimidine and purine metabolism pathways when compared to grouped pen crocodiles, linked to altering energy associated induced stress. Additionally, fecal microbiome analysis indicated increased Firmicutes:Bacteroides (F:B) ratio in group-housed animals, suggesting greater stress.DiscussionThe study highlights that while traditional stress indicators like corticosterone levels may not differ significantly between housing conditions, metabolic and microbiome analyses provide deeper insights into stress responses. Single pens are associated with less metabolic disruption and potentially better health outcomes compared to group pens. These findings underscore the value of fecal microbiome and metabolomics in assessing animal welfare in farmed crocodiles.